2019
DOI: 10.1002/ece3.4941
|View full text |Cite
|
Sign up to set email alerts
|

Structure and genetic variability of golden mussel (Limnoperna fortunei) populations from Brazilian reservoirs

Abstract: The golden mussel, Limnoperna fortunei a highly invasive species in Brazil, has generated productive, economical, and biological impacts. To evaluate genetic structure and variability of L. fortunei populations present in fish farms in the reservoirs of Canoas I (CANFF), Rosana (ROSFF), and Capivara (CAPFF) (Paranapanema River, Paraná, Brazil), eight microsatellite loci were amplified. Five of those eight loci resulted in 38 alleles. The observed heterozygosity (Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The lack of geographic genetic structure was also noticed by Furlan-Murari and colleagues after sequencing 5 microsatellite loci from 3 golden mussel populations over the Paranapanema river [15]. Zhan and colleagues have sequenced 8 microsatellite loci and the mitochondrial cytochrome c oxidase subunit I (COI) gene from 22 South American populations and found 2 supposedly different genetic clusters [13].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The lack of geographic genetic structure was also noticed by Furlan-Murari and colleagues after sequencing 5 microsatellite loci from 3 golden mussel populations over the Paranapanema river [15]. Zhan and colleagues have sequenced 8 microsatellite loci and the mitochondrial cytochrome c oxidase subunit I (COI) gene from 22 South American populations and found 2 supposedly different genetic clusters [13].…”
Section: Discussionmentioning
confidence: 82%
“…Zhan and colleagues have compared 22 South American populations and found support for relevant human-mediated transportation [13]. Subsequent studies have strengthened this conclusion, although the number of genetic clusters identified has differed [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The golden mussel a highly invasive species in Brazil and has caused productive, economical, and biological impacts in reservoirs (Furlan-Murari et al, 2019). Cage fouling increases production costs as they reduce the durability of structures and require frequent cleaning of the screens.…”
Section: Introductionmentioning
confidence: 99%
“…Limnoperna fortunei (dunker 1857) belongs to the Mollusca phylum, bivalve class, and mussel family. The adult mussel is 8-30 mm long, closely connected by byssus, stacked in layers, with a clumpy length of up to 15 cm and a thickness of 3-5 cm [1]. A large number of Limnoperna fortunei invade and deposit in pipes, culverts, tunnels, and other structures of water transmission projects, causing structural blockage and corrosion, resulting in serious biological fouling, affecting the normal operation of water transmission projects [2,3].…”
Section: Introductionmentioning
confidence: 99%